The Circassian genocide - Richmond, Walter (Genocide, political violence, human rights series., 2013)
This book chronicles the history of the war between Russia and Circassia, describes in detail the final genocidal campaign, and follows the Circassians in diaspora through five generations as they struggle to survive and return home. It updates the story to the twenty-first century as the Circassian community works to gain international recognition of the genocide as the region began preparations for the 2014 Winter Olympics in Sochi, the site of the Russians' final victory over the Circassians.